English for specific purpose: a learning-centered approach - Tom Hutchinson (Cambridge Univ. Press, 1993)
The book discusses the evolution of ESP and its position today; the role of the ESP teacher; course design; syllabuses; materials; teaching methods, and evaluation procedures